32 & 16 YEARS AGO. - Holmes, Neville (Computer (00189162), 2009)
The article features the contents of the December 1977 and December 1993 issues of "Computer" magazine. The December 1977 issue includes articles on the activities of the Education Committee of the IEEE Computer Society and the launch of desktop computers by Hewlett-Packard. Articles featured in the December 1993 issue include one on computer program visualization and another on computer-aided software engineering.